Peningkatan Manajemen Usaha Melalui Integrasi Sistem Informasi Manajemen dan Keuangan di Kelompok Tani Sumber Kembang - Nur Faizin; Ardhiarisca, Oryza; Mei Yuana, Dia Bitari; Lestari, Datik; Putra, Rediyanto (Politeknik Negeri Jember, 2024)
The Sumber Kembang Farmers Group is a coffee producer located in Sukorambi District, Jember. The problems faced by partners are related to business management. The presence of workers at the agreed time is an absolute law for calculating worker honor. However, this is difficult to achieve if it is not supported by a good management information system. Therefore, the solution offered in this activity is the creation and training of a management information system in the form of a worker attendance application and an MS Access-based financial application. Furthermore, managers provide training regarding how to use management information systems and financial applications. The target achieved is to improve the business management of the Sumber Kembang Farmers Group. The output of this service activity is a service journal, online mass media articles, and videos of the service implementation.